Netherlandish carved altarpieces a historiographic overview with a focus on Sweden - De Moor, Hannah (2021)
Netherlandish carved altarpieces have attracted much new scholarly attention over the last decades. The objective of this article is first to provide a comprehensive historiography of the existing body of research, and second to outline the main research trends from the late nineteenth century until now. Even though Sweden still houses no less than thirty-eight late medieval Netherlandish carved altarpieces, about ten retable fragments, and two wooden Malines statuettes,and much has already been written on the pieces preserved there, an extensive description of this research field is currently lacking. The third aim of this paper is to fill the remaining gap by providing an extensive status quaestionis of the research on Netherlandish carved altarpieces in Sweden.